Proposta para implementação de drenagem sustentável em atendimento a critérios urbanísticos: estudo de caso bairro Jardim Caranã - Souza, Kétlen Cristiany Brito de (2023)
The city of Boa Vista, in the state of Roraima, has undergone an intense process of urbanization and its urban fabric has a conventional drainage system. This urbanization, among which the construction of buildings, paving, soil waterproofing and current drainage systems stand out, unbalance the natural environment and drastically change the urban water dynamics. From the year 2006 several municipalities created their Master Plans for Urban Drainage, however, until then, Boa Vista did not adapt. In this sense, this research proposes to show the current urban situation of the area under study, in terms of its physical-territorial aspects, seeking, among the existing alternatives, the types of sustainable drainage suitable for the urban watershed of Boa Vista/RR, having as premises of choices urban, social, economic and environmental factors, in the end, to elaborate a proposal of alternative sustainable drainage techniques for the residents of the Jardim Caranã neighborhood, meeting the urban standards of the municipality. For this, it was necessary to carry out field tests to collect data and verify the percolation of water in the soil, and with the results obtained, make use of the sustainability concepts of the Sustainable Drainage Systems considered more adequate to the local reality. After carrying out the characterization of the urban situation and the physical-territorial aspects of the neighborhood, the total green area (IAVT) and vegetation cover (ICV) indices were obtained, the impacts on the floodplain found in loco, data collection of soil waterproofing and the calculation of sustainable drainage techniques. As a result, for urban issues, a suboptimal IAVT was found, different from the ICV, which was considered above. As for waterproofing, the neighborhood was considered very permeable, when the rates of permeability and occupation of the lot were surveyed. The infiltration capacity in the neighborhood was found, and later, the rain garden and infiltration trench techniques were calculated, demonstrated through a technical project and by the calculations it can be confirmed that the infiltration trench is more efficient, for being able to store a greater volume of water. However, the two techniques can cooperate a lot in the infiltration of these waters that drain superficially inside the lot.